Lipoproteins as Risk Indicators of Atherosclerosis in Middle Age Adults, A Clinical Cross Section Study - Sohaib Akbar, Rabea Rashed, Yasir Raheem Malik, Kashif Aziz Ahmad, Uzair Mumtaz, Nayyer Riffat, Arslan Shuja (Pakistan Journal of Medical & Health Sciences, 2022)
Aims and Objectives: The aims and objectives of current study was to assess the relationship of lipoproteins with atherosclerosis as a risk factors of cardiovascular diseases in local population for health awareness. This study was conducted from June 2021 to March 2022 in medical units of Lahore General Hospital Lahore, Pakistan. Materials and Methods: Total 172 male individuals were selected for present study and divided them into two different groups. 72 normal male individuals were placed in Group-C while remaining 100 male individuals with cardiovascular diseases were in Group-A. Blood serum levels of Cholesterol. Triglycerides, Low Density Lipoproteins and High Density Lipoproteins of each person were measured through Colorimetric kit method. Collected raw data was presented bio-statistically with the applications of SPSS version 2021. Results: The metabolic biomarkers, Blood serum levels of Cholesterol. Triglycerides, Low Density Lipoproteins and High Density Lipoproteins of Group-C and Group-A (200.10±0.01, 150.01±0.02, 130.01±0.04, 45.04±0.03) and (280.10±0.01, 200.11±0.04, 180.02±0.01, 35.01±0.04) were obtained. The measured data of Group-A showed a significant (p<0.05) difference than the control group. On the other hand t-test difference for non-metabolic biomarkers i.e. Smokers, Sample size, Cardiac syndrome and Gender (-45,-28,-28,-28) of both groups have higher t-score. Conclusion: In this prospective clinical research of Pakistani middle-aged men in Lahore, findings have correlation between cardiovascular diseases and high blood serum levels of cholesterol, triglycerides, LDL and low levels of HDL.